Використання AR технологій в сучасному мистецтві - Кругова, І. О. (ХНУРЕ, 2020)
The modern world cannot be imagined without innovative digital technologies, industrial production and marketing. With the development of these three spheres, people need more content, which is also evolving. In the new decade, more and more attention is being paid to 3D visualization technologies. But humanity is tired of being in the real space – we strive to gain experience in virtual and other realities. There are two main points of the spectrum of different realities (these two points are only units in vast mixed reality).
Keywords: віртуальна; 3D; доповнена; реальність